IMPLIKASI MORATORIUM PENERIMAAN CPNS TERHADAP OPTIMALISASI REFORMASI BIROKRASI - Dewi Sendhikasari Dharmaningtias (Jurnal Politica, 2011)
Moratorium of new recruitment of civil servant (CPNS) has been set by the government in the framework of budget savings and improving management of human resources (HR). The HR policies is carried out under the direction of policy in the grand design and road map of the national bureaucratic reforms. The aims of this article to analyze steps and the implications taken by the government in managing the re-organization of PNS and Its staff by issuing the moratorium policy. This policy, in addition to cut personnel expenditure budget, is also intended to restructure civil servants and their organization in order to optimize the bureaucratic reform agenda.